Competition between precipitation and dissolution in Cu–Ag alloys under high pressure torsion. (1st January 2017) - Straumal, B.B.; Pontikis, V.; Kilmametov, A.R.; Mazilkin, A.A.; Dobatkin, S.V.; Baretzky, B.
Abstract: Severe plastic deformation (SPD) always leads to the strong grain refinement in the materials. Logically, in two- and multiphase alloys SPD has to cause the fragmentation and dissolution of precipitates in a matrix. However, it has been observed recently, that, contrary to this generally accepted viewpoint, SPD can lead also to the decomposition of supersaturated solid solution. In this work we analyze for the first time (both experimentally and theoretically) the competition of these simultaneous processes can take place, namely (1) the dissolution of precipitates and (2) decomposition of supersaturated solid solution with precipitation of a second phase. As a result, a dynamic equilibrium between these two processes appears, and a certain steady-state concentration in a solid solution is reached. In this work we study the high pressure torsion (HPT) of a two-phase Cu–3.9 at. % Ag alloy in two different states: (i) as-cast consisting of a (Cu) solid solution with diluted 1.9 at.% Ag and another 2 at.% Ag as fine silver precipitates and (ii) an almost homogeneous solid solution with diluted 3.9 at.% Ag obtained by homogenization at T  = 780 °C, 900 h and subsequent water quenching. HPT at room temperature causes the partial dissolution of precipitates in the as-cast samples and partial decomposition of the solid solution in homogenized samples. After HPT, the solute concentration in the matrix is the same in both samples (about 2.9–3.0 at.% Ag). Thus, it does not depend on the initial state and is higher than the equilibrium solubility limit at the HPT temperature. This concentration is equal to solubility limit at the effective temperature of T eff  ≈ 680 °C. We also proposed the model describing the dynamic equilibrium between dissolution and precipitation in HPT. Assuming that HPT fixes the composition at matrix-precipitate interfaces, we show that HPT-enhanced diffusive transport of species is the process likely controlling the observed steady-state composition in the matrix and precipitate average diameter. Graphical abstract: Vegard law for the (Cu) solid solutions in Cu–Ag alloys. The composition of (Cu) solid solutions after high pressure torsion (HPT) does not depend on that before HPT. Image 1